2022
DOI: 10.1007/s00520-022-07176-2
|View full text |Cite
|
Sign up to set email alerts
|

Care provided by older adult caregivers to a spouse in active cancer treatment: a scoping review

Abstract: Purpose Due to population aging, the number of older adults with cancer will double in the next 20 years. There is a gap in research about older adults who are the caregiver of a spouse with cancer. Therefore, this review seeks to answer the overarching research question: What is known about the association of providing care on Health-Related Quality of Life (HRQOL), psychological distress, burden, and positive aspects of caregiving for an older adult caregiver to a spouse with cancer? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(221 reference statements)
0
6
0
Order By: Relevance
“…Whether the intervention can improve the emotional burden of the patients themselves deserves special attention. As shown in Table S1 , structured psychological intervention (including psychological support, health education for patients and their families, stress handling, coping skills, experience exchange, anticancer declaration learning), 22 , 34 , 41 , 42 , 44 relaxation training, 39 , 40 , 41 , 43 , 44 communication and exchange, 23 , 34 , 39 , 45 mindfulness therapy, 20 , 23 dignity enhancement and independence enhancement, 46 cognitive behavioral therapy (CBT), 21 and a nursing model intervention based on the Rosenthal effect 47 had been used to intervene the emotional burden of the patients. Structured psychological interventions, which integrated several components (such as health education, stress management, and coping skills), were beneficial in decrease of patients' emotional burden scores and could improve negative emotions (such as anxiety, depression, anger, confusion) in multiple ways.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether the intervention can improve the emotional burden of the patients themselves deserves special attention. As shown in Table S1 , structured psychological intervention (including psychological support, health education for patients and their families, stress handling, coping skills, experience exchange, anticancer declaration learning), 22 , 34 , 41 , 42 , 44 relaxation training, 39 , 40 , 41 , 43 , 44 communication and exchange, 23 , 34 , 39 , 45 mindfulness therapy, 20 , 23 dignity enhancement and independence enhancement, 46 cognitive behavioral therapy (CBT), 21 and a nursing model intervention based on the Rosenthal effect 47 had been used to intervene the emotional burden of the patients. Structured psychological interventions, which integrated several components (such as health education, stress management, and coping skills), were beneficial in decrease of patients' emotional burden scores and could improve negative emotions (such as anxiety, depression, anger, confusion) in multiple ways.…”
Section: Resultsmentioning
confidence: 99%
“…39 , 40 , 41 , 44 Providing opportunities of communication for the patients also helped to ease patients' psychological stress and to increase channels for emotional catharsis. 23 , 34 , 39 , 45 For mindfulness therapy, two studies both found that it was beneficial to improve the pessimism of patients to a certain extent. 20 , 23 One study found that after the dignity therapy intervention, the sense of dignity of the patients rose (mean ​= ​−0.52 (−1.01; −0.02)), the sense of being a burden fell (mean ​= ​−0.26 (−0.49; −0.02)), depression eased (mean ​= ​−1.17 (−2.07; −0.26)), feeling anxious relaxed (mean ​= ​−1.00 (−1.67; −0.33)), and the feeling like a burden to others (n ​= ​12, mean ​= ​−0.58 (−1.09; −0.08)) improved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, healthcare providers are supposed to be aware of, assess and subsequently address SPB among lung cancer patients undergoing immunotherapy. Available SPB related interventions generally focused on cognitive behavioral therapy [53], functional exercise [54], and communication and exchange [55].…”
Section: Discussionmentioning
confidence: 99%